Coumarin derivatives from the leaves and twigs of Murraya exotica L. and their anti-inflammatory activities. (September 2020) - Liang, Haizhen; Shi, Yuntao; Zeng, Kewu; Zhao, Mingbo; Tu, Pengfei; Jiang, Yong
Abstract: Fifteen previously undescribed coumarin derivatives, murratins A−M, including two pairs of coumarin enantiomers with a cyclopropane unit, two benzocoumarins, a dimeric coumarin, and eight C-8-substituted coumarins, together with six known analogues were isolated from the extract of the leaves and twigs of Murraya exotica L., a medicinal plant named " Jiulixiang " in Chinese. Their structures were elucidated on the basis of comprehensive analysis of 1D and 2D NMR and HRMS spectroscopic data, and the absolute configurations were assigned via comparison of the specific rotations, the ECD exciton coupling method, comparison of experimental and calculated ECD data, and the ECD data of in situ formed transition metal complexes. All the isolates were evaluated for their inhibitory effects on lipopolysaccharide-induced nitric oxide production in RAW 264.7 cells, and five coumarin derivatives showed moderate inhibitory activities. The possible mechanism for NO inhibition of undescribed bioactive compounds was deduced to interact with iNOS protein via molecular docking. The above results shed some light on a better understanding of the traditional anti-inflammation effect of M. exotica and coumarins are disclosed to be its potential anti-inflammatory constituents. Graphical abstract: Fifteen previously undescribed coumarin derivatives were isolated from Murraya exotica . Their NO inhibition activity and docking with iNOS protein were evaluated. Image 1 Highlights: Fifteen previously undescribed coumarin derivatives were isolated from Murraya exotica . Two pairs of coumarin enantiomers with cyclopropane unit were resolved by chiral HPLC. Five compounds showed moderate inhibition on NO production. The possible mechanism was interaction with iNOS protein via molecular docking.